Article 28 of the ITE Law as a Pillar of Consumer Protection in Online Transactions - Nurkhalifah Kaharu, Siti; Rusdiyanto U Puluhulawa, Mohamad; Hidayat Muhtar, Mohamad (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
The development of online buying and selling transactions has also given rise to a rise in fraud cases that are detrimental to consumers. Article 28 paragraph (1) of Law Number 19 of 2016 concerning ITE needs to be legally reviewed to determine the extent to which these provisions are able to provide protection for consumers from fraudulent acts in online transactions. Therefore, this study aims to legally analyze the provisions of Article 28 paragraph (1) of Law Number 19 of 2016 concerning Information and Electronic Transactions (UU ITE) as a form of legal protection for consumers in dealing with the rampant fraud in online buying and selling transactions. The main problems in this study include how the concept of legal protection for consumers is formulated in the article and what are the legal implications for perpetrators of fraud. This study uses a normative method with a legislative, conceptual, and case approach. Data were obtained from primary, secondary, and tertiary legal materials through literature studies. The results of the study indicate that Article 28 paragraph (1) of the ITE Law provides legal protection through a prohibition on the dissemination of false information that is detrimental to consumers in electronic transactions, with a maximum prison sentence of six years and/or a fine of up to one billion rupiah as regulated in Article 45A paragraph (1). In addition to being a repressive instrument, this provision is also preventive in nature by demanding that sellers be responsible for conveying honest and accurate information. This study emphasizes the urgency of law enforcement and digital literacy in strengthening consumer protection amidst the rapid growth of e-commerce.